Impact of income on the profile of cardiovascular risk factors among hypertensives in a Nigerian tertiary health centre: a cross-sectional study - Karaye, KM (Clinics Cardive Publishing, 2009)
BACKGROUND: In most developed countries, risk factors for cardiovascular diseases (CVD) are more prevalent in low socio-economic classes. However, the pattern in developing countries appears to be different. This study sought to evaluate and compare risk factors for CVD as well as absolute CVD risk in hypertensive subjects grouped by income in Kano, Nigeria. METHODS: The study was cross-sectional in design and carried out in Aminu Kano Teaching Hospital, Kano, Nigeria. Seventy treatment-naïve hypertensives and an equal number of hypertensives on treatment were recruited by balloting from the outpatient clinics, and then regrouped into low- and high-income earners. These two groups were then compared in terms of their profile of CVD risk factors and absolute CVD risk. All the assessed CVD risk factors are recognised in standard guidelines for the management of persons with systemic hypertension. RESULTS: The low-income group comprised 45 patients (32.1%) while the remaining 95 (67.9%) had a high income. The most prevalent CVD risk factor was dyslipidaemia, found in 77.8 and 71.6% of low- and high-income earners, respectively (p = 0.437). The prevalence of proteinuria was significantly higher among low-income earners (42.2%) compared with highincome earners (15.8%) (p = 0.001). Mean serum creatinine was also higher among low-income earners but the difference did not reach statistical significance (p = 0.154). Very high CVD risk was found in 75.6 and 70.5% of low- and high-income earners, respectively (p = 0.535). CONCLUSION: Dyslipidaemia and very high CVD risk were found in over 71% of the patients regardless of their level of income. Low-income earners had a higher prevalence of indices of renal damage. These findings pose a great challenge to the present and future management of all subjects, particularly those in the low-income group, given that in Nigeria, healthcare is largely paid for directly out of their pockets.